Impact response of polymeric foam core structures - Ang, Pauline Bao Lian (2009)
To identify the potential benefits of a material, it is essential to measure its properties through laboratory experiments and validate the experimental results using analytical or finite element modeling. In this project, the material behavior of Divinycell F90, an extruded Polyethersulfone (PES) foam, were studied through uniaxial compression and double lap shear experiments as a function of three specimen thicknesses, 0.003 m, 0.005 m and 0.012 m. After which, the low-velocity impact response of Divinycell F90 polymeric foam core sandwich structure was investigated.